Caries in the primary dentition, after discontinuation of water fluoridation, among children receiving comprehensive dental care - Seppa¨ L, Ka¨rkka¨inen S, Hausen H (Blackwell Synergy, 2000)
The city of Kuopio in central Finland had fluoridated piped water for 33 years, beginning in 1959. Due to strong opposition by various civic groups, water fluoridation was stopped at the end of 1992. There is little information on the consequences of stopping fluoridation in a community with comprehensive dental care for all children and adolescents, who are frequently exposed to different fluoride measures both at home and in the dental office.